BUS TICKET BOOKING APPLICATION ONLINE WITH THE PHP LANGUAGE - Gatot Harri Susatyo; Elly Agustina, Skom., MMSi (Jurnal Sistem Informasi, 2003)
Bus ticket booking is an activity that must be done if you want to use buses to travel long distances, but in their activities in the conventional booking is an activity that takes enough time, effort and cost. Condition of bus transportation services company in Indonesia, especially in his ministry is still using the technology that is unreliable, making it difficult for customers who busy with their daily routine. In this case a discourse for the writer to develop the service functions of bus transportation services company to facilitate its customers to book bus tickets according to needs.